ANALISIS PERBANDINGAN KINERJA KEUANGAN MENGGUNAKAN METODE PEARLS PADA CREDIT UNION HATI AMBOINA DAN CREDIT UNION AIN HOV AIN DI PROPINSI MALUKU - Steven Siaila (Soso-Q : Jurnal Manajemen, 2017)
This study aims to benchmark financial performance on two Cradit Union in the Province of Maluku namely CU Ain Hov Ain with CU Hati Amboina  by using PEARLS Analysis Approach. The types of Ratios used for benchmarking are Protection Ratios; The ratio of outstanding loans; Asset Quality Ratio; Return and cost ratio Net SHU Ratio; Asset Growth Rate.Results obtained from calculations using the PEARLS method; The CU AHA Protection Ratio is in a better position than CU HA from the outstanding Loan Ratio it appears that CU HA delivers more cautious credit so it is in a position not far from ideal standard while CU AHA is far above the ideal standard set, asset CU HA is better than CU AHA asset quality. Asset Quality Ratio in AHA CU shows that fluctuating  with tendency continue to rise while CU HA is also very fluctuating with spike in extreme but the increase further; The development of return and cost ratio shows that the development of CU HA has increased higher than CU AHA so that for this ratio CU AHA has a good cost ratio compared to CU HA; The net SHU ratio can be said that the development of CU HA is better and potentially better in the future; Asset Growth Ratio then it is concluded that the growth of AHA CU is better than CU HA. From the above explanations it can be concluded that CU HA has better financial performance compared to CU AHA KeywordsCredit Union Activity - Financial Report - PEARLS Method - Financial Performance